Heterodera glycines Ichinohe, 1952 (Nematoda: Tylenchida) from Argentina. 1. Morphological and morphometrical characterisation of second-stage juveniles - Lax, Paola; Doucet, Marcelo E (Nematology : international journal of fundamental and applied nematological research, 2001)
Abstract Second-stage juveniles from two populations of Heterodera glycines races 1 and 3 from different areas in Argentina were characterised on the basis of an analysis of morphological and morphometrical characters. Some of the morphological characters assessed were found to be subject to intra- and inter-population variability. It was not possible to detect clear differences between the populations of the two races under consideration. Most of the morphometrical characters showed ranges different from those known for other populations of the species and reduced variability. The analysis of variance revealed significant statistical differences for most of the morphometrical characters studied.